Correlation of Clinicopathological Factors with Brain Tumor-Related Epilepsy in Glioma. (30th September 2022) - Wang, Zengliang; Yang, Wensheng; Wang, Yongxin; Aili, Yirizhati; Wang, Zhitao; Wang, Quanyi; Jiang, Shunli; Zhang, Guangning; Zhang, Junchen; Li, Bo
Abstract : Objectives . Glioma patients with brain tumor-related epilepsy (BTRE) have a complex profile due to the simultaneous presence of two pathologies, glioma and epilepsy; however, they have not traditionally received as much attention as those with more malignant brain tumors. The underlying pathophysiology of brain tumor-related epilepsy remains poorly understood. The purpose of this study was to investigate the possible correlation between molecular neuropathology and glioma with BTRE and a wide range of BTRE-associated molecular markers of glioma patients. Methods . A retrospective cohort study of 186 glioma patients was evaluated at our hospital, of which 64 had BTRE. The chi-square test, Spearman rank correlation, and multivariate logistic analyses were used to identify clinicopathological factors associated with BTRE in glioma patients. Results . Of the 186 patients examined in this study, 64 (34.4%) had BTRE. Based on the analysis of the characteristics of these patients, the results showed that patient age (over 40 years; P = 0.007 ), low WHO grade (grade I, II; P = 0.001 ), IDH-1 positive mutation (P = 0.027 ), low ATR-X expression level (OR = 0.44 ; 95% CI: 0.21, 0.92), and low Ki-67 PI (OR = 0.25 ; 95% CI: 0.10, 0.68) were associated with the occurrence of BTRE. In our cohort, BTRE patients did not differ by sex, tumor location, or expression of olig-2 and CD34. The results of the matching study showed that low Ki-67 PI and negative ATR-X expression levels were independent factors for a higher incidence of preoperative seizures in glioma patients. Conclusion . The current study updates existing information on genetic markers in gliomas with BTRE and explores the correlation of a wide range of clinicopathological factors and glioma patients with BTRE and suggests three putative biomarkers for BTRE: positive IDH1 mutation, low Ki-67 PI, and negative ATR-X expression. These factors may provide insights for developing a more thorough understanding of the pathogenesis of epilepsy and effective treatment strategies aimed at seizure control.